Valorization of Moss biomass as a natural porous Matrix for shape-stable phase change material (PCM) composites - Can, Ahmet; Ganguly, Sauradipta; Gencel, Osman; Sari, Ahmet; Erata, Huseyin (Elsevier, 2026)
Phase change materials (PCMs) are used to improve energy efficiency, particularly in building heat storage and passive thermal management applications. In this study, moss biomass (Calliergonella cuspidata (Hedw.) Loeske) (Ca) was evaluated as a natural porous matrix, and a novel non leachable composite phase change material (PCM) was developed based on n-octadecane (n-OD). The moss biomass was impregnated with 60% n-OD by direct mixing method, and its structural stability was enhanced by the addition of Sodium silicate (SS) at 10% and 30% (by wt%) respectively. The morphological, chemical, and thermal properties of the composites were characterized by SEM, EDS, FTIR, DSC, TGA, XRD, and thermal conductivity analyses. SEM-EDS results showed that the moss biomass (Ca) had high porosity, with the addition of SS resulting in a more compact and homogeneous structure. FTIR analyses exhibited the formation of Si-O-Si bands, indicating successful integration of SS into the matrix. According to DSC analysis, the Ca/n-OD(60%) composite had a melting temperature of 26.1 degrees C and a melting enthalpy of 153.7 J/g whereas for the SS-added variants, these values were measured as 148.3 J/g (10%) and 144.2 J/g (30%), respectively. The enthalpy losses of only 2-3 J/g after 700 heating-cooling cycles indicated high thermal stability. TGA and XRD analyses showed that the addition of SS increased the thermal resistance of the composites, creating an amorphous network structure. The results indicate that moss-based Ca/ n-OD/SS composites, with their compact, leak-free structure, high heat storage capacity, and excellent cyclic stability, hold promise as eco-friendly materials for subsequent applications in: thermal energy storage for buildings, solar energy systems, and the thermal management of electronic components.
Keywords: Phase Change Material; Moss Biomass; Sodium Silicate; N-Octadecane